"Colossal" interstitial supersaturation in delta ferrite in stainless steels—I. Low-temperature carburization. (March 2015) - Wang, D.; Chen, C.-W.; Dalton, J.C.; Yang, F.; Sharghi-Moshtaghin, R.; Kahn, H.; Ernst, F.; Williams, R.E.A.; McComb, D.W.; Heuer, A.H.
Abstract: Low-temperature carburization has been successfully used to surface harden 17-7 precipitation-hardening (PH) and 2205 duplex stainless steels. After carburization, the delta ferrite grains in both alloys near the free surface show a uniform weak contrast under conventional transmission electron microscopy (TEM). Spatially resolved compositional analysis shows that these delta ferrite grains possess enormous carbon contents (as high as 18 at.%) in solid solution, but structurally there is no detectable tetragonality (<5%) or evidence of carbide formation. Near the interface between the interstitially hardened layer and bulk material, weak-contrast plates with significant carbon concentrations were observed in ferrite grains in 17-7 PH stainless steel. A carbon-induced spinodal-like decomposition of delta ferrite to the nanometer-scale Cr-rich and Fe-rich alpha ferrite phases is observed. Carbon is enriched in Cr-rich ferrite due to the high affinity between C and Cr, which introduces lattice mismatch between the Cr-rich and Fe-rich regions. The weak contrast is believed to be the result of overlapping strain fields of these Cr-rich and Fe-rich phases. As the binding energies of carbon interstitials to dislocations in body-centered cubic Fe-based alloys are greater than the binding energy of C to Fe in possible carbides, segregation to dislocation cores is expected. The extremely high dislocation density we observe in high-resolution scanning TEM is consistent with the hypothesis that carbon segregation to dislocation cores effectively delays carbide precipitation and makes possible the "colossal" carbon supersaturation.